Optimalisasi Calming Corner untuk Meningkatkan Kemandirian Emosional Anak dalam Kurikulum PAUD - Nisrina Mutia Afifah; Kartika Fajriani; Lina Revilla Malik (Lembaga Yasin AlSys, 2026)
Although Calming Corner has begun to be used in early childhood education practice, in-depth studies on its role in supporting children’s emotional stability at school remain limited. This study aims to examine the role and strategies for utilizing Calming Corner as a means of supporting children’s emotional independence in the current early childhood education curriculum. This study used a library research method by reviewing fifteen scientific literature sources published in the last five years. The results of the review show that the most effective arrangement of Calming Corner is an integrated model that combines the Montessori principle of order, the flexibility of the Kaizen method, and the support of modern sensory teaching aids. The findings also reveal a shift in the function of Calming Corner, from merely a classroom display element to a recovery space that helps children recognize their own condition and calm themselves independently. The conclusion of this study affirms that Calming Corner serves as a “second teacher” that supports a shift in classroom management approaches, from strict external supervision toward the development of children’s internal self-regulation. Theoretically, this review enriches the literature on calming learning environments, while practically, it provides guidance for teachers in integrating a non-punitive emotional pause space into KOSP documents. These findings imply the strengthening of educational practices that care for children’s mental health and support the realization of the independent Profil Pelajar Pancasila.